2017
DOI: 10.1016/j.jct.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Propane, n -butane and i-butane stabilization effects on methane gas hydrates

Abstract: The goal of this work is to analyse the hydrate equilibria of methane + propane, i-butane and n-butane gas mixtures. Experimental hydrate equilibrium data was acquired for various compositions of these components in methane, ranging from 0.5-6.8 mol%. Applying this information with the Clausius-Clapeyron equation, the extent of hydrate promotion was demonstrated quantitatively by calculating the slope of the equation and the dissociation enthalpy (ΔHd). Methane equilibria was found to be most sensitive towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Here, it should be also noted that both 33DMEB and 12EB/ c23EB exhibited higher promotion capacities than 22DMB 60,61 and n-butane, 62 respectively, despite the similarity in molecular sizes and geometries. This trend has consistently been reported in other (oxirane + CH 4 ) vs (simple alkane + CH 4 ) systems, such as PO vs propane, 17 EIB vs i-butane, 17 12ECP vs CP, 15 12ECH vs cyclohexane.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Here, it should be also noted that both 33DMEB and 12EB/ c23EB exhibited higher promotion capacities than 22DMB 60,61 and n-butane, 62 respectively, despite the similarity in molecular sizes and geometries. This trend has consistently been reported in other (oxirane + CH 4 ) vs (simple alkane + CH 4 ) systems, such as PO vs propane, 17 EIB vs i-butane, 17 12ECP vs CP, 15 12ECH vs cyclohexane.…”
Section: Resultsmentioning
confidence: 68%
“…Equilibrium P–T conditions of the CH 4 hydrates (a) containing 33DMEB and 22DMB ( x = 0.029); (b) containing 12EB, c 23EB, t 23EB, DEB (x = 0.056), and n -butane. The data for none (simple CH 4 hydrate), 22DMB, , and n -butane (CH 4 / n -butane = 94.5/5.5) are from previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…While there is an overlap between data used in this study and several others published in the field, other equilibrium data sources published in recent years or overlooked in the past have been included. All data sources have been referenced. ,,,, …”
Section: Methodsmentioning
confidence: 99%
“…All equilibrium data used in this investigation have been obtained from the following sources. All sources of equilibrium data used in the development of models in this research have been referenced. ,,,, It must be emphasized that not all data from each source is included in the dataset, for instance, several measurements from the popular Deaton and Frost study have been excluded due to a lack of separation of iso butane and n -butane.…”
Section: A1mentioning
confidence: 99%
“…They observed that the equilibrium curves shifted toward the higher-pressure region due to the combined effects of pores and electrolytes . Smith et al found that the equilibrium line of methane is sensitive to small concentrations (0.5 mol %) of propane and i-butane, and they further observed that the structural stability of sII hydrate intensifies as the concentration of propane and i-butane increases . A multitude of thermodynamic inhibitors and promoters has been identified to exert a notable impact on the hydrate equilibrium conditions, thereby influencing the formation and dissociation of hydrates. Gas hydrate formation involves the consumption of gas and water.…”
Section: Introductionmentioning
confidence: 99%